1995
DOI: 10.1136/bmj.310.6991.1357
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vitamin D receptor genotype on bone mineral density in postmenopausal women: a twin study in Britain

Abstract: The findings that in postmenopausal women in Britain bone density-particularly at the hip and spine-is genetically linked and specifically associated with the vitamin D receptor genotypes should lead to novel approaches to the prevention and treatment of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
3
5

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(101 citation statements)
references
References 12 publications
6
87
3
5
Order By: Relevance
“…27 All were recruited from a national media campaign, gave written informed consent and were unaware of any hypotheses regarding body fat.…”
Section: Methodsmentioning
confidence: 99%
“…27 All were recruited from a national media campaign, gave written informed consent and were unaware of any hypotheses regarding body fat.…”
Section: Methodsmentioning
confidence: 99%
“…115 VDR gene polymorphisms have been found to be associated with the serum 25(OH)D 3 concentration and with bone mineral density, although the strength of this association was originally overestimated. [116][117][118][119][120][121] If vitamin-D deficiency is a risk factor for tuberculosis, it should be expected that VDR gene variants would be associated with tuberculosis. VDR polymorphisms were therefore typed in the Gambian case-control study in which NRAMP1 was found to be associated with tuberculosis.…”
Section: Vitamin-d Receptormentioning
confidence: 99%
“…Spector и соавт. в Британии также оценивали связь МПКТ у женщин-близнецов в постменопаузе с гене-тическими особенностями РВД: установили разную степень зависимости для показателей МПКТ, но на-иболее она была выражена для проксимального отде-ла бедренной и лучевой кости; аллели, полиморфные по TaqI для tt, составляли 19,5 %, Тt -41,0 % и ТТ -39,5 % [20].…”
Section: Introductionunclassified